CULTIVATING EFL PRE-SERVICE TEACHERS’ SOCIAL PRESENCE IN ONLINE CLASSROOM MANAGEMENT PRACTICE THROUGH PROJECT-BASED LEARNING - Banatul Murtafi'ah; Ferbiana Nerissa Arvenina (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2021)
The current pandemic situation has forced EFL preservice teachers to conduct their teaching practice virtually. By teaching virtually means that they must have the ability to manage classroom online. However, to the best of researchers’ knowledge, these pre-service teachers did not get any preparation related to online classroom management. One of the must-have abilities for pre-service teachers to manage online classroom is social presence. Since during online teaching the social contact between teachers and students weaken, then the ability for the teachers to socially present before their students is urgent. Though several studies have proposed that students’ social abilities could be supported through project-based learning, there is a limited study investigating project-based learning and social presence. Therefore, through this research, the researchers attempted to develop a course focusing on developing pre-service teachers’ social presence while practicing online classroom management through four stages of project-based learning activities. Using a social presence questionnaire adapted from Swan et al. (2008) and Arbaugh (2008), after one semester, the results show that there was a significant difference between preservice teachers’ pre-test and post-test score of social presence. It is also found that female pre-service teachers have higher social presence level than male pre-service teachers. In addition, 87% of the pre-service teachers joining the study also acknowledged that the project-based learning activities they did during the course help them develop their social presence. At the end, several implications related to the research findings are proposed in this paper.